2010
DOI: 10.1007/s11249-009-9570-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Head/Disk Interface for Patterned Media

Abstract: The use of patterned media is a new approach proposed to extend the recording densities of hard disk drives beyond 1 Tb/in. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…6 some nonlinearity is observed, especially for higher pattern height. This nonlinear effect was also obtained by the direct simulation (Murthy et al 2010) and it was explained as: a change of the bit pattern diameter leads to a change of the pattern profile not only in the slider's width direction but also the slider's length direction so that the side flow is prevalent in this case. However, for small pattern height, the flying height change can still be considered as a linear function of the recess area ratio.…”
Section: Model Techniquesmentioning
confidence: 54%
See 1 more Smart Citation
“…6 some nonlinearity is observed, especially for higher pattern height. This nonlinear effect was also obtained by the direct simulation (Murthy et al 2010) and it was explained as: a change of the bit pattern diameter leads to a change of the pattern profile not only in the slider's width direction but also the slider's length direction so that the side flow is prevalent in this case. However, for small pattern height, the flying height change can still be considered as a linear function of the recess area ratio.…”
Section: Model Techniquesmentioning
confidence: 54%
“…This paper showed that a mesh size to bit diameter ratio smaller than 1:6 required to guarantee a sufficiently high resolution of the air bearing pressure. To reduce the numerical complexity of the direct method, Murthy et al (2010) transferred the pattern from the disk surface to the slider surface and limited the region of the pattern to the center trailing pad of the slider. All the above researches showed the effect of the pattern height and pattern area ratio on the slider's flying height.…”
Section: Introductionmentioning
confidence: 99%
“…The Reynolds equation satisfactorily reflects hydrodynamic lubrication effects for a broad range of interface parameters, and its solution delivers the pressure, which allows the interface to carry a normal load . Based on the Reynolds equation, a number of recent studies have directly concentrated on the optimization of the mesoscopic interface geometry by fully or partially endowing the surface typically with pillar‐type features that have circular or square cross‐sections . However, a homogenization‐based scheme that concentrates on the microscale through the design of micro‐textures with the purpose of attaining a prescribed macroscopic interface response appears not to have been addressed in the literature.…”
Section: Introductionmentioning
confidence: 99%